If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(2x-1)2/3=x1/3
We move all terms to the left:
(2x-1)2/3-(x1/3)=0
We add all the numbers together, and all the variables
(2x-1)2/3-(+x1/3)=0
We get rid of parentheses
(2x-1)2/3-x1/3=0
We multiply all the terms by the denominator
(2x-1)2-x1=0
We add all the numbers together, and all the variables
-1x+(2x-1)2=0
We multiply parentheses
-1x+4x-2=0
We add all the numbers together, and all the variables
3x-2=0
We move all terms containing x to the left, all other terms to the right
3x=2
x=2/3
x=2/3
| (18)=2x+4 | | 7-b/19=20 | | -5a+5+a=5 | | 42+6m=-3m+15 | | -2(x+1)=-4x+8 | | 26y+2(90+-13y)=180 | | g/5-3=42 | | 0.7-5=0.2x+1 | | 2(5-2x)+3x=8 | | 7(x+3)-4(3x+3)=34 | | 13=v/8 | | 3a-2÷4-4a+5÷6=-5 | | 45=y-5 | | n/4-7=-11 | | -8=k/11 | | 1-2n+5=36 | | -¾(x-3)-5=⅛(x-1) | | 4(7-k)=22 | | 4(2x+3)+2(x-7)=18 | | 8/n=72 | | x=15=21 | | 6(2l-10)=150 | | 8–y=16+3y | | 7(z+2)−3z=44. | | 6(2l-10)=-2 | | 2c+5=10c-59 | | 8e-4=26-2e | | x(4+6)=28 | | 30-2x=42 | | -3-1=0,66n | | -8=m+12 | | 47x-16x=-310 |